Statistical estimation of regional disproportions in bank lending in Ukraine - A.V. Nepran; A.I. Litvinov (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
The article examines the processes of regional differentiation in bank lending. The creation of a special fund with mandatory involvement of bank representatives in management has been justified for the first time. The purpose of creating such a fund is to create more favorable conditions for lending in the regions. Based on statistical analysis, the conclusion is drawn that the type of regional development of bank lending in Ukraine, according to the studied parameters, can be unequivocally characterized as asymmetric. The main problem of interregional disparities in lending in Ukraine is the large volume of lending in Kyiv and several other industrial centers, coupled with the slow development of the provinces. Regional asymmetry in banking lending poses a serious threat and a critical challenge that Ukraine is already facing. Disparities in banking lending create several problems for the country, including a slowdown in national economic growth rates due to the need to allocate funds to reduce regional asymmetry, rather than stimulating development; the withdrawal and redistribution of financial resources; the emergence of depressed areas; an increase in social tension in the country; the intensification of disintegration processes, and so on. The study found that significant amounts of credit resources in Kyiv are used for trading and intermediation activities (trade financing, real estate transactions). However, the intensification of interregional differentiation in banking lending does not promote the transition of the economy to an innovative type of development. To overcome negative trends, it is necessary to ensure an inflow of credit resources to regions with a weakened resource base, which will contribute to accelerating their socio-economic development. To activate banking lending in other regions, it is proposed to create a special fund, which will provide economic incentives for lending activation. This will contribute to the redistribution of credit resources in other regions, which will help reduce asymmetry in regional development.